A COMPREHENSIVE APPROACH INTO STEREOSCOPIC VISION - Wulandari, Lely Retno (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2022)
Stereopsis (or stereoscopic) vision is the ability to see depth of perception, which is created by the difference in angle of view between both eyes. The first process is known as simultaneous perception. Objects will fall on each corresponding retina and there will be a process of fusion of the two images into one. Then, the brain initiates three-dimensional perception in visual cortex, creating stereoscopic vision. Stereoscopic vision will rapidly develop, especially at the age of 6-8 months of life. Stereoscopic is important in daily activities. There are many stereoacuity tests to evaluate stereoscopic vision. Stereoscopic examinations are based on the principle of haploscope, anaglyph, or polaroid vectograph. There are qualitative and quantitative examination methods to assess stereoscopic vision. Qualitative examinations such as Horizontal Lang Two Pencil test and Synoptophore. Quantitative examination including Contour stereopsis test and Clinical random dot stereopsis test. The inability of the eye to see stereoscopic can be called stereoblindness. This can be affected by amblyopia, decreased visual acuity, or the presence of ocular misalignment. Inability to achieve stereoscopic vision will impact an individual to perform some daily life activities, and lead to an increase in difficulty interacting in the world.